Zahra: a Shattered Body and Voice from Lebanon - Rebeiz, Mireille (Pivot: A Journal of Interdisciplinary Studies and Thought, 2017)
This article examines the gradual disintegration of Zahra, a girl from Lebanon. It studies the role of mothers in patriarchal societies and the impact of their conservative education on their daughters’ emotional and psychological growths. Raised to believe in her inferiority due to her femaleness, Zahra constantly tries to live up to the social expectations for the female gender. Each subsequent trial ends in failure. When the civil war breaks out in Lebanon, the resulting societal chaos temporarily relieves Zahra from the duties of her gender. Only this break is shortly lived as Zahra is killed.